Effect of Polyethylene glycol to Hydroxyapatite water filter - Mohd Zaaim Mat Daud (Universiti Malaysia Perlis, 2008)
The effect of different percentage of binder (PEG) on the microstructure of hydroxyapatite (HA) and its density was examined. In this study, HA samples was prepared by wet mixing methods and samples was prepared using slip casting process. The particle size of HA powder was analized using Malvern Mastersizer 2000. From particle size result observed the average particle size was 9.881 µm. Sample was prepared in two conditions by using binder and without binder. By using binder, the percentages of binder were 1-5% of PEG. The samples were prepared in spherical shape to make it suitable for water filtration. After drying in oven for 4 hours, sample was sintered at temperature 1200°C for 6 hours. Then, the samples have been tested for its density. The sample without binder has maximum density compared to other samples which added with PEG. The maximum density of sample added with PEG was at 4% percentage binder. The samples with 4-5% PEG and without PEG have lower porosity compared to samples with 1-3% PEG. From micrograph of scanning electron microscope (SEM) the distribution of porosity was highest for sample with 1 % PEG. The micrograph also shows that the samples without binder have better particle-to-particle bonds. It also has lesser amount of pores and has smaller macropores size. From all this, the highest strength of sample would be the sample without binder. It is also possible to develop materials in which the porosity is varied as a function of filtration of impurities in water.